MODELING REGIONAL COMMODITY PRICE VOLATILITY IN EAST JAVA - Sugeng Hariadi; Mela Yunita (Universitas Gunadarma, 2026)
Commodity markets in major production regions are characterized by price volatility arising from perishability, seasonal production, and distribution constraints. While agricultural price volatility has been widely examined at the national level, evidence on regional differences across commodity groups remains limited. This study investigates the volatility dynamics of food and horticultural commodity prices across eight regions in East Java using daily price data from 2018 to 2024. Price series are transformed into logarithmic returns, and volatility is estimated using symmetric and asymmetric GARCH family models. The results reveal significant differences across both commodity groups and regions. Food commodities are consistently best represented by symmetric GARCH models, indicating that volatility is primarily driven by the magnitude of price shocks. In contrast, horticultural commodities are better explained by asymmetric GARCH models, demonstrating that both the magnitude and direction of shocks influence volatility. Horticultural commodities also exhibit greater sensitivity to new information and stronger volatility persistence than food commodities. Moreover, volatility dynamics differ substantially across regions, reflecting variations in production systems and market conditions. These findings highlight the importance of commodity specific and region-specific price stabilization policies to strengthen regional food market resilience